Robustness analysis for linear time-invariant systems with structured incrementally sector bounded feedback nonlinearities - Chen, Xin; Wen, John T. (Zielona Góra: Uniwersytet Zielonogórski)
This paper addresses the stability analysis of a negative feedback interconnection of a multivariable linear time-invariant system and a structured time-invariant incrementally sector bounded nonlinearity. The classic Zames-Falb multiplier is extended to the multivariable case and is approximated by linear matrix inequalities.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka